2016
DOI: 10.1186/s12968-017-0417-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of mitral regurgitation in patients with hypertrophic cardiomyopathy using aortic and pulmonary flow data: impacts of left ventricular outflow tract obstruction and different left ventricular segmentation methods

Abstract: BackgroundCardiovascular magnetic resonance (CMR) imaging in patients with hypertrophic cardiomyopathy (HCM) enables the assessment of not only left ventricular (LV) hypertrophy and scarring but also the severity of mitral regurgitation. CMR assessment of mitral regurgitation is primarily based on the difference between LV stroke volume (LVSV) and aortic forward flow (Ao) measured using the phase-contrast (PC) technique. However, LV outflow tract (LVOT) obstruction causing turbulent, non-laminar flow in the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…While the application of MRI for detecting LVOT obstruction is limited, it is challenging to use objective parameters to evaluate obstruction. Fortunately, previous studies have shown that LVEF, LVMI, and maximum LVWT or average LVWT were significantly higher in obstructive HCM than that in nonobstructive HCM, as in our study, 18,21,22 In this study we further investigated the correlation between LVOT obstruction and these parameters, and the result showed that Average LVWT and Maximum LVWT can serve as independent risk factors for obstruction.…”
Section: Discussionsupporting
confidence: 57%
“…While the application of MRI for detecting LVOT obstruction is limited, it is challenging to use objective parameters to evaluate obstruction. Fortunately, previous studies have shown that LVEF, LVMI, and maximum LVWT or average LVWT were significantly higher in obstructive HCM than that in nonobstructive HCM, as in our study, 18,21,22 In this study we further investigated the correlation between LVOT obstruction and these parameters, and the result showed that Average LVWT and Maximum LVWT can serve as independent risk factors for obstruction.…”
Section: Discussionsupporting
confidence: 57%
“…They used the MR Standard method to quantify the regurgitant volume and demonstrated similar bias (bias = 0 ml, −18 ml to 17 ml) for intraobserver tests. Śpiewak et al have previously demonstrated that the exclusion of papillary muscles and trabeculations from the blood pool and the inclusion of them in the LV mass calculation can lead to significantly lower MR volume than when papillary muscles and trabeculations are included in the blood pool [16]. This discrepancy again limits the clinical translation of both MR Standard and MR LVRV for the quantification of MR between two sites using different methods to LV segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Downloaded from aorta the measurement is performed, 4 5 and the phenomenon is even more pronounced under pathological conditions. [5][6][7][8] While a recent consensus statement recommends measuring forward aortic volume at the level of the sinotubular (ST) junction, 9 different measurement locations in the aorta are regularly used (table 1). In some studies, measurements from different locations are used indiscriminately, 10 and some studies do not report the location of flow measurement.…”
Section: How Might This Impact On Clinical Practice?mentioning
confidence: 99%